Molecular pathology a practical guide for the surgical pathologist and cytopathologist - Bartlett, John M. S.; Shaaban, Abeer; Schmitt, Fernando (Cambridge University Press, 2015)
This practical manual provides a comprehensive yet concise guide to state-of-the-art molecular techniques and their applications. It starts with an overview of the essential principles of molecular techniques, followed by separate chapters detailing the use of these techniques in particular tissues and organs, and describing recommended treatment plans. Each chapter covers the tests available, their advantages, limitations, and use as diagnostic and prognostic tools, with key learning points at the end of each topic. Using both histologic and cytologic samples, it discusses how to interpret test results in a pathologic context and enables trainees and practising pathologists to gain an in-depth understanding of molecular diagnostic techniques and how to incorporate them into routine diagnostic practice. Aiding the daily practice of refining diagnosis, as well as offering a didactic approach, this book is an essential reference for practising pathologists and cytopathologists as well as trainees in pathology